2022
DOI: 10.33200/ijcer.942575
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Philosophy for Children (P4C) Curriculum on Critical Thinking through Philosophical Inquiry and Problem Solving Skills

Abstract: The effect of philosophy for children (P4C) curriculum on critical thinking through philosophical inquiry and problem solving skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…So, results of this study are confirmed by the previous research. Also, it is possible to find other studies concluding trainings designed to develop CT also improved PS (Işıklar & Abalı Öztürk, 2022;. Therefore, the fact that activities designed to develop CT improve both CT and PS support the existence of a strong relationship between these higher-order thinking skills.…”
Section: Discussionmentioning
confidence: 90%
“…So, results of this study are confirmed by the previous research. Also, it is possible to find other studies concluding trainings designed to develop CT also improved PS (Işıklar & Abalı Öztürk, 2022;. Therefore, the fact that activities designed to develop CT improve both CT and PS support the existence of a strong relationship between these higher-order thinking skills.…”
Section: Discussionmentioning
confidence: 90%
“…Barrow (2012) states that philosophy education for children contributes to the development of students' self-expression and self-esteem, arouses curiosity and enable them develop positive attitude towards the lesson. Işıklar & Öztürk (2022) and Jones (2015) and Kiyarsi (2017) states that in a society that makes inquiries, students are aware of their self-awareness and social awareness skills and are in a socially positive relationship with their peers. Kilby (2019) and Paine (2012) stated that philosophy education for children motivates students towards the lesson, makes the lesson more interesting and provides understanding of the subject.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Komponen kunci berpikir kritis adalah kemampuan untuk mengevaluasi pernyataan orang lain. Informasi yang diperoleh dari orang lain tidak selalu akurat, sehingga penting bagi seseorang untuk memberikan alasan tentang hal tersebut secara kritis (Işiklar & Abali Öztürk, 2022). Kemampuan berpikir kritis sangat diperlukan dalam menganalisis suatu permasalahan sampai dengan mencari solusi untuk menyelesaikan permasalahan tersebut.…”
Section: Pendahuluanunclassified